Land, labour, war and displacement: A history of four black concentration camps in the South African War (1899-1902) (Historia, 2021)
From the outset of the South African War both the British and Boer forces deliberately and directly targeted civilians during their military operations, thus heralding a harbinger of twentieth century "total war". Well established in the historiography are the camps established by the British for internment of the Boers, later known as concentration camps. Less known are the so-called "native" refugee camps, which functioned as forced wartime labour camps, and are today known as black concentration camps. Although civilian internment was not genocidal by design and purpose, the high loss of life and bitterness among the Boer descendants shaped the political narrative of twentieth century South Africa. Yet the black forced labour camps were far more lethal and designed along a completely different model to those where the Boers were interned. The memory of this experience has only in the last two decades entered historical discourse about the conflict, however. This article examines those camps which interned black civilians at Orange River Station, Taung, Vryburg and Brussels Siding. Situated approximately 300 kms apart at their southern and most northerly points, the sites of these camps were first identified by the author in the period from 2001 to 2008.